ANALYSIS OF THE VIEWS ON THE IMAMATE IN LAMISHI'S "TAMHID" - Abdullo Gulomov (Scholar Express Journal, 2022)
Currently, the falsification of sacred islamic concepts and their interpretation for malicious purposes is on the rise. These concepts include some erroneous categories, in particular, "caliphate", misinterpreted by Hizbut-tahrir. Based on the work of Mahmud Lamishi "at-Tamhid li qawaid attawhid", this article explains the views of the Ahl al-Sunnah wa al-Jama’ah on the imamatee (leadership) and the caliphate.
Keywords: Lamishi; Islamic philosophy; Hanafi-Maturidi; Tamhid